A Centrifuge Model Test of the Ground Motion Response in a Moderately Stiff Soil - Jing-Yan Lan; Ting Wang; Diwakar Khatri Chhetri; Mohammad Wasif Naqvi; Liang-Bo Hu (Shock and Vibration)
The ground motion response in a moderately stiff soil in seismic events has been traditionally studied based on the actual field records which, however, have yet to offer consistent results regarding the amplification effect of the ground motion. In the present study, a centrifuge model of the moderately stiff soil field is designed to study the amplification effect of the ground motion in response to seismic loads. Four El Centro waves of different strengths are used as the input wave at the base under a gravitational field of 75 g. Ground motion data at different depths are collected via a number of sensors to study the acceleration peak, time history, and response spectrum of the ground motion. The measured amplitude and energy of seismic waves are found to gradually increase from the bottom to the surface during the propagation of seismic waves, and the peak acceleration at the surface is significantly magnified. The response spectrum analysis shows that the acceleration response spectrum gradually moves to the high-frequency direction from the base to the surface and the value of the response spectrum decreases with the increase of the depth in the present study.